2020
DOI: 10.1016/j.vetmic.2020.108893
|View full text |Cite
|
Sign up to set email alerts
|

A novel PCV2 ORF5-interacting host factor YWHAB inhibits virus replication and alleviates PCV2-induced cellular response

Abstract: Highlights YWHAB is a PCV2 ORF5-interacting host factor. YWHAB expression is activated by PCV2 infection and ORF5 transfection. YWHAB inhibits PCV2 replication. YWHAB alleviates PCV2 infection induced ERS, autophagy, ROS production and apoptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Five host proteins including cytochrome P450 1A1 (CYP1A1), glycoprotein-NMB (GPNMB), serine and arginine rich splicing Factor 3 (SRSF3), tyrosine 3-monooxygenase/tryptophan 5-monooxygenase activation protein β (YWHAB), and zinc finger protein 511 (ZNF511) have been found to be able to interact with PCV2 ORF5 by yeast two-hybrid screening ( Table 1 ) [ 144 ]. Among them, both GPNMB and YWHAB can inhibit PCV2 replication by binding with ORF5 [ 150 , 151 ]. GPNMB might be involved in cell proliferation and anti-inflammatory responses [ 152 ].…”
Section: Porcine Circovirus Type2 Open Reading Frame5mentioning
confidence: 99%
“…Five host proteins including cytochrome P450 1A1 (CYP1A1), glycoprotein-NMB (GPNMB), serine and arginine rich splicing Factor 3 (SRSF3), tyrosine 3-monooxygenase/tryptophan 5-monooxygenase activation protein β (YWHAB), and zinc finger protein 511 (ZNF511) have been found to be able to interact with PCV2 ORF5 by yeast two-hybrid screening ( Table 1 ) [ 144 ]. Among them, both GPNMB and YWHAB can inhibit PCV2 replication by binding with ORF5 [ 150 , 151 ]. GPNMB might be involved in cell proliferation and anti-inflammatory responses [ 152 ].…”
Section: Porcine Circovirus Type2 Open Reading Frame5mentioning
confidence: 99%
“…Additionally, the host transmembrane glycoprotein NMB (GPNMB) can interact with the ORF5 and restrict PCV2 infection by increasing Cyclin A and reducing of S phase of the cell cycle [ 100 ]. Moreover, 14-3-3β/α protein (also known as YWHAB, tyrosine 3-monooxygenase/tryptophan 5-monooxygenase activation protein) can inhibit PCV2-induced ERS, autophagy, ROS, and apoptosis by directly interacting with the ORF5 protein, thus suppressing the virus infection [ 101 ].…”
Section: Crosstalk Between Pcv and Hostmentioning
confidence: 99%
“…ORF5 activates autophagy through AMPK-ERK1/2-mTOR and PERK-eIF2a-ATF4 pathways, thus promoting PCV2 replication (Lv et al, 2020). However, another study showed that ORF5 directly binds to host regulatory factor 14-3-3b (YWHAB), which inhibits ERS, ROS, and autophagy, thus inhibiting virus replication (Guo et al, 2020). In addition, PCV2 infection increases the expression of pDNAJB6 in PK-15 cells, and the C-terminal J domain of pDNAJB6 binds to the cap protein, which increases the formation of autophagy and promotes virus replication (Han et al, 2020).…”
Section: Current Knowledge Of Autophagy In Different Animal Virusesmentioning
confidence: 99%
“…Rabies virus (RABV) is a neurophagic virus that can infect people and animals and cause fatal rabies (Li et al, 2017). It is a member Increases PCV2 replication PCV2 activates autophagy through activating AMPK and increasing host oxidative stress Qian et al, 2017;Geng et al, 2020;Guo et al, 2020;Han et al, 2020;Lv et al, 2020;Zhang et al, 2020c) PCV2 induces mitophagy by increasing ROS production and the phosphorylation of Drp1 ORF5 activates autophagy through AMPK-ERK1/2-mTOR and PERK-eIF2 a-ATF4 pathways ORF5 inhibits autophagy by binding to YWHAB Cap activates autophagy through binding to pDNAJB6 Cap induces complete autophagy via inhibition of p-mTOR Pig Classical swine fever virus (CSFV)…”
Section: Porcine Rna Virusesmentioning
confidence: 99%